Infinite Sequence Solutions for Space-Time Fractional Symmetric Regularized Long Wave Equation (Journal of Partial Differential Equations, 2016)
" In this paper, we investigate the space-time fractional symmetric regularized long wave equation. By using the B\u00e4cklund transformations and nonlinear superposition formulas of solutions to Riccati equation, we present infinite sequence solutions for space-time fractional symmetric regularized long wave equation. This method can be extended to solve other nonlinear fractional partial differential equations."